Deep-Sea Fan-Valley Conglomerate: Cap Enrage Formation, Gaspe, Quebec - Johnson, Barry A. (My University, 1974)
The conglomerates of the Cambro-Ordovician Cap Enrage Formation, Gaspe, Quebec, were deposited and are now localized in basic depositional units called 'pods'. Pods are discontinuous in a longitudinal (parallel to flow) direction and a lateral direction where they also decrease in size, coarseness and abundance. Maximum average pod dimensions are approximately 400 m in longitudinal length and 100-200 m in width. Penecontemporaneous erosion has reduced pod thickness to a remanent maximum average of approximately 5 m. Preferred clast fabric consists of longaxes parallel to flow and dipping upcurrent; it is best developed in the well-sorted coarse pebble conglomerate and is the single quantifiable paleocurrent indicator in the conglomerate.
The orientated descriptive framework evolves around the pod which has a broadly, concave-up base and an omnidirectional, continuous facies change from cobble/boulder conglomerate dominating the pods' center/base through to the horizontal equivalent and veneer of sandstone. Peripheral pod termini also commonly occur as scoured, delicate featheredge alternations of conglomerate and sandstone. Massive fabric disorganization is common at the pods' center/base. Cobble/pebble train stratification becomes apparent near the facies transition from cobble to coarse pebble conglomerate and grades into and/or alternates with subparallel quartz granule layer stratification which in turn gently converges towards the pod periphery and increases in abundance vertically. Grading is best developed in the coarse pebble conglomerate facies and is defined by normal coarse-tail and distribution grading of clast size and by an inverse-like grading of abundance of quartz granules and clasts. It appears that inverse grading in its descriptive-genetic sense is absent.
The sedimentological 'thalweg model' has an overall fining and thinning upward character and has four divisions. Division 'W' consists of the conglomerate horizons' basal few pods which are very coarse grained and have sharp, erosional, undulatory and, commonly, diapirically deformed bases. Division 'X' consists of conglomerate pods and interbedded sandstone beds and exhibits no consistent vertical change between pods and/or beds in clast size, facies relationships, sedimentary structure occurrences or pod morphology. Division 'Y' consists of vertically thinning and fining conglomerate pods in decreasing abundance interbedded with sandstone. Division 'Z' is a sandstone horizon composed of beds of pebbly sandstone and coarse, massive sandstone with and without dish-structure.
The conglomerate pods are interpreted to be the infill remanents of scour depressions deposited by mass flows which had their conglomerate deposition generally restricted to the thalweg channel of a fan-valley. The sandstone is preserved in the fan-valley as deposits within and adjacent to the thalweg channel. The thalweg channel meanders with an approximate 40° change in trend over a 7 Km straight-line distance and migrates discontinuously as a result of intermittent, very powerful mass flows breaking away from established channels and carving a new thalweg channel elsewhere in the fan-valley.
Title: Deep-Sea Fan-Valley Conglomerate: Cap Enrage Formation, Gaspe, Quebec, Author: Barry A. Johnson, Location: Thode